Touchscreen Interface and Product Textural Incongruence Effect on Product Haptic Perceptions - Germirli, Selin (CV ODIS, 2024)
The wide spread of online shopping causes more customers to browse and purchase products through devices with touchscreens (e.g., smartphones, tablets) every day at an ever-increasing pace, allowing them to touch only touchscreen interfaces rather than textures of products. Touchscreen interfaces are glasslike and may feel different than the products consumers evaluate. This haptic incongruence between the touchscreen interface and the product's expected texture can cause the haptic dimensions of a product to become more salient and might affect haptic perceptions. This research aims to explore the effect of product-touchscreen interface textural congruence on haptic perceptions of the product. It consists of three experimental studies showing the significant relationships between the incongruence of touchscreen interface texture and product haptic properties, haptic vividness, haptic elaboration, perceived ownership through identification, physical control, and knowledge. These consequently positively influence the attitude toward the product, purchase intention, and endowment.